AVALIAÇÃO POLÍTICA DO PROGRAMA FARMÁCIA POPULAR DO BRASIL À LUZ DOS PRINCÍPIOS DO SISTEMA ÚNICO DE SAÚDE - Aragão Junior, Gilvan Alves (2012)
The Popular Pharmacy of Brazil Program was created in 2004 with the purpose of reducing of treatment abandonment caused by the impact that the acquisition of medications for chronic diseases occasioned in the long run, the budget of families who sought to obtain these medicines in the network private. In the 2006, the program was expanded through the creation of an axis called Has Popular Pharmacy Here , which allowed private pharmacies establish agreements with the Ministry of Health for distribution of medications subsidized with resources of this program. The central issue about this program is the fact that it uses the system of copayment in its engineering, which means that users of the program must spend a small amount to get the medication needed, resulting in double taxation of the same social benefit, since the citizen finances the production of medications at the moment that pays taxes and makes a second payment at the moment of the acquisition of such medications. This work makes a political evaluation of this program from the principles established by the Unified Health System, to which all services and action of health of the country must be submitted. To reach this objective I opted for an evaluation with qualitative approach and a methodology called political evaluation of the policy (SILVA, 2008), in which I use as technical the bibliographical research and the documentary research to collect information that allows the elucidation of the evaluative dimensions defined for this study, namely: the determinants that conditioned the formulation of the policy, ethical and political framework and the principles of social justice base that it, the model of intervention of the program and its strategies of action and, finally, its sources of resources and its way of financing. I conclude with this evaluation that the Popular Pharmacy of Brazil Program had as main determinative the neoliberal politics that foments the reduction of State action through, among other measures, the creation of programs that perform the management of public services in partnership with private institutions, imposing to the population a part of the financing of the given services. In addition, the program in question violates the three doctrinal principles of the Unified Health System, does not possess legal endorsement for the accomplishment of economic subventions, being therefore illegal, beyond the fact of that the Federal Constitution to hinder the destination of public resources for private institutions with lucrative ends, which is done by the program, of where if also concludes that it is unconstitutional. Finally, the Court of Accounts of the Union points that there are no studies to justify the existence of the program, because there is no evidence of better cost-effective compared it with the programs that provide medications free of charge for the Brazilian population.